Impact of advance care planning on dying in hospital: Evidence from urgent care records. - Martina Orlovic; Tom Callender; Julia Riley; Ara Darzi; Joanne Droney (PLoS ONE, 2020)
Place of death is an important outcome of end-of-life care. Many people do not have the opportunity to express their wishes and die in their preferred place of death. Advance care planning (ACP) involves discussion, decisions and documentation about how an individual contemplates their future death. Recording end-of-life preferences gives patients a sense of control over their future. Coordinate My Care (CMC) is London's largest electronic palliative care register designed to provide effective ACP, with information being shared with urgent care providers. The aim of this study is to explore determinants of dying in hospital. Understanding advance plans and their outcomes can help in understanding the potential effects that implementation of electronic palliative care registers can have on the end-of-life care provided. Retrospective observational cohort analysis included 21,231 individuals aged 18 or older with a Coordinate My Care plan who had died between March 2011 and July 2019 with recorded place of death. Logistic regression was used to explore demographic and end-of-life preference factors associated with hospital deaths. 22% of individuals died in hospital and 73% have achieved preferred place of death. Demographic characteristics and end-of-life preferences have impact on dying in hospital, with the latter having the strongest influence. The likelihood of in-hospital death is substantially higher in patients without documented preferred place of death (OR = 1.43, 95% CI 1.26-1.62, p<0.001), in those who prefer to die in hospital (OR = 2.30, 95% CI 1.60-3.30, p<0.001) and who prefer to be cared in hospital (OR = 2.77, 95% CI 1.94-3.96, p<0.001). "Not for resuscitation" individuals (OR = 0.43, 95% CI 0.37-0.50, p<0.001) and who preferred symptomatic treatment (OR = 0.36, 95% CI 0.33-0.40, p<0.001) had a lower likelihood of in-hospital death. Effective advance care planning is necessary for improved end-of-life outcomes and should be included in routine clinical care. Electronic palliative care registers could empower patients by embedding patients' wishes and personal circumstances in their care plans that are accessible by urgent care providers.